"Using New Eyes": Photography as a Spiritual Practice for Faith Formation and Worship. (March 2014) - Crowley, Eileen D.
Abstract This article presents three cases of how Lutheran groups used photography as a spiritual practice in processes that led to group spiritual reflection for faith formation and worship: a photography club; a Photography as a Spiritual Practice mini‐course in a parish; and a six‐month parish project of communal art‐making of liturgical media art for one church's Easter Vigil readings.